EVA prefabricated coiled material for plastic court track and preparation method thereof

By using ethylene-vinyl acetate copolymer and polytetrafluorovinyl base material in plastic runway coils, combined with hydrophobic agents and anti-aging agents, the problem of reduced compatibility of coils at high temperatures is solved, and the radiation resistance of coils is improved The lighting and anti-aging performance achieves excellent sun protection and ultraviolet protection.

CN118852784BActive Publication Date: 2024-12-13HUNAN YOUGUAN SPORTS MATERIAL CO LTD
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
CN202411346861.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-13
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

When preparing the existing plastic runway coil, UV-531 has poor high temperature resistance. Compatibility may decrease or migrate when combined with other chemical additives, which affects its lasting effect and leads to mechanical properties. Decreased and shortened lifespan.

Method used

Using ethylene-vinyl acetate copolymer and polytetrafluoroethylene as the base material, hydrophobic agent, anti-aging agent and modified lignin are added, and sodium lignin sulfonate, SiO2/ZnO composite nanoparticles, zirconium propionate, nanometers Hydrophobic agents and anti-aging agents composed of chitosan and nanotitanium dioxide, coordinated with modified lignin to improve the radiation resistance, hydrophobicity and anti-aging properties of the coil.

Benefits of technology

It improves the tensile strength, particle size uniformity and anti-aging properties of the coil, enhances the absorption capacity of ultraviolet rays, and significantly improves the sun protection, ultraviolet resistance and anti-bacterial properties of the coil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118852784B_ABST
    Figure CN118852784B_ABST
Patent Text Reader

Abstract

The invention discloses an EVA prefabricated coil for a plastic court track and a preparation method thereof, which solves the problem that when an ultraviolet absorber UV-531 is added during the preparation of the existing coil, the high temperature resistance is poor, and when it is compounded at high temperature or with other chemical additives, the compatibility may be reduced or migration may occur, thereby affecting the lasting effect of the coil in the coil. The coil comprises the following raw materials: ethylene-vinyl acetate copolymer, polytetrafluoroethylene, a hydrophobic agent, a cross-linking agent, a foaming agent, an antioxidant, and modified lignin. In an embodiment of the invention, an EVA prefabricated coil for a plastic court track is provided, which uses ethylene-vinyl acetate copolymer and polytetrafluoroethylene as base materials, and adds a hydrophobic agent, an antioxidant and modified lignin, so that the prepared EVA prefabricated coil has high tensile strength and uniform particle size, and the modified lignin in the raw materials has a strong ability to absorb ultraviolet rays, so that the coil has excellent sunscreen and UV protection properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of runway coils, and in particular relates to an EVA prefabricated coil for a plastic court runway and a preparation method thereof. Background Art

[0002] Traditional plastic tracks need to be laid layer by layer. Due to the complexity of construction, blistering and particle loss may occur during use, which increases maintenance costs. The rolls of prefabricated plastic tracks have long been prefabricated. Prefabricated plastic tracks have obvious advantages over traditional plastic tracks in terms of material properties, construction and installation, sports performance, environmental protection performance and maintenance costs. At the same time, prefabricated plastic tracks are a type of track surface material made of plastic as the main raw material. Due to its excellent properties, they are currently widely used in sports venues. EVA (ethylene-vinyl acetate copolymer) material is a commonly used material for prefabricated plastic tracks. Due to its good elasticity and shock absorption properties, it is widely used in the construction and laying of sports venues, especially tracks.

[0003] Chinese patent CN111117175B discloses a prefabricated coil and a preparation method thereof. The prefabricated coil is composed of the following components in parts by mass: rubber particles: 10-60 parts; thermoplastic polyester elastomer foam particles: 10-50 parts; polyurethane adhesive: 5-20 parts. The preparation method of the prefabricated coil comprises the following steps: uniformly mixing the rubber particles and the thermoplastic polyester elastomer foam particles, and then adding the polyurethane adhesive to mix uniformly to obtain a mixture; adding the mixture to a molding device, performing compression molding, then heating to perform curing molding, and then cooling and cutting. However, when the existing coil is prepared, the ultraviolet absorber UV-531 is added, and the high temperature resistance is poor. When it is compounded at high temperature or with other chemical additives, the compatibility may be reduced or migration may occur, which affects its lasting effect in the coil, thereby accelerating the aging of the coil, resulting in a decrease in the mechanical properties of the coil and a shortened life. In view of the above problems, we propose an EVA prefabricated coil for a plastic court track and a preparation method. Summary of the invention

[0004] The purpose of the present invention is to provide an EVA prefabricated coil for a plastic court track and a preparation method in view of the shortcomings of the prior art, so as to solve the problem that the existing coil has poor high temperature resistance when adding ultraviolet absorber UV-531 during preparation, and may have reduced compatibility or migration when compounded with other chemical additives at high temperature, thereby affecting its lasting effect in the coil.

[0005] When the existing coiled materials are prepared, the ultraviolet absorber UV-531 is added, which has poor high temperature resistance. When it is mixed with other chemical additives at high temperature, the compatibility may be reduced or migration may occur, which will affect its lasting effect in the coiled materials, thereby accelerating the aging of the coiled materials, resulting in a decrease in the mechanical properties of the coiled materials and a shortened lifespan. In view of the above problems, we have proposed an EVA prefabricated coiled material for plastic court tracks and a preparation method. In short, the EVA prefabricated coiled material for plastic court tracks includes the following raw materials: ethylene-vinyl acetate copolymer, polytetrafluoroethylene, a hydrophobic agent, a cross-linking agent, a foaming agent, an antioxidant, and modified lignin. In an embodiment of the present invention, an EVA prefabricated coil for a plastic court track is provided, which is based on ethylene-vinyl acetate copolymer and polytetrafluoroethylene, and is added with a hydrophobic agent, an antioxidant and modified lignin, so that the prepared EVA prefabricated coil has high tensile strength and uniform particle size. At the same time, the hydrophobic agent, the antioxidant and the modified lignin work together to ensure the radiation resistance, hydrophobicity and anti-aging properties of the EVA prefabricated coil, and the modified lignin in the raw material has a strong ability to absorb ultraviolet rays, so that the coil has excellent sun protection and UV protection properties.

[0006] The present invention is implemented in this way: an EVA prefabricated coil for a plastic court runway, wherein the EVA prefabricated coil for a plastic court runway comprises the following raw materials in parts by weight: 100-150 parts of ethylene-vinyl acetate copolymer, 1-10 parts of polytetrafluoroethylene, 10-30 parts of a hydrophobic agent, 1-20 parts of a cross-linking agent, 5-12 parts of a foaming agent, 1-5 parts of an antioxidant, and 2-5 parts of modified lignin;

[0007] The hydrophobic agent comprises the following raw materials in weight percentage:

[0008] Quaternized sodium lignin sulfonate: 40%;

[0009] SiO2 / ZnO composite nanoparticles: 50%;

[0010] Zirconium propionate: 10%;

[0011] The antioxidant comprises the following raw materials in weight percentage:

[0012] Nano chitosan: 50%;

[0013] Nano titanium dioxide: 20%;

[0014] Acrylic acid: 15%;

[0015] Butylated hydroxyanisole: 15%.

[0016] Preferably, the EVA prefabricated coil for the plastic court track includes the following raw materials in parts by weight: 110-140 parts of ethylene-vinyl acetate copolymer, 3-8 parts of polytetrafluoroethylene, 12-25 parts of hydrophobic agent, 4-15 parts of cross-linking agent, 6-11 parts of foaming agent, 2-4 parts of antioxidant, and 3-4 parts of modified lignin.

[0017] Preferably, the method for preparing the hydrophobic agent specifically comprises:

[0018] Take sodium lignin sulfonate, dissolve the sodium lignin sulfonate in 6 times the volume of deionized water, place the sodium lignin sulfonate aqueous solution on a 60°C magnetic stirrer and stir for 20 minutes, add 0.5 times the volume of ethanol to the sodium lignin sulfonate aqueous solution, stir for 30 minutes at room temperature, and collect the precipitate by suction filtration to purify the sodium lignin sulfonate;

[0019] The purified sodium lignin sulfonate is compounded with a 30% sodium hydroxide aqueous solution to obtain a 30wt% sodium lignin sulfonate alkaline solution, the sodium lignin sulfonate alkaline solution is placed in an oil bath and heated to 80°C, epichlorohydrin and trimethylolpropane are mixed in a 30% sodium hydroxide aqueous solution at a volume ratio of 3:1 to obtain quaternized polyepichlorohydrin, the quaternized polyepichlorohydrin is added to the sodium lignin sulfonate alkaline solution, the sodium lignin sulfonate alkaline solution is stirred at a stirring speed of 10-20r / min, the reaction is kept warm for 4h, and then cooled to room temperature, the reaction solution is dialyzed, and rotary evaporated to obtain quaternized sodium lignin sulfonate;

[0020] Zirconium dioxide and propionic acid are mixed in a reactor, the stirring speed is controlled to be 100-120 r / min, ethanol is added to assist the reaction, the reactor is heated to 45° C., after the reaction is completed, the reactor is cooled to room temperature, and zirconium propionate is separated by suction filtration;

[0021] Put silica, anhydrous ethanol and deionized water in a three-necked flask, stir the mixed solution at a speed of 100-120 r / min for 1.5 h. After stirring, a silica solution is obtained. Ammonia water is used to adjust the pH value of the silica aqueous solution to 8.5 at 55 ° C. γ-aminopropyltriethoxysilane is taken and added dropwise into the three-necked flask. After reacting for 2.5 h, the three-necked flask is heated to 80 ° C. The silica is modified to obtain an amino-modified silica solution.

[0022] Take zinc oxide, disperse it in 8 times the volume of deionized water, stir it evenly for 30 minutes, then add the zinc oxide suspension dropwise into the amino-modified silica solution, stir it evenly for 2 hours by ultrasonic, and wash it with deionized water and anhydrous ethanol in a volume ratio of 1:1 to obtain SiO2 / ZnO composite nanoparticles;

[0023] SiO2 / ZnO composite nanoparticles were dissolved in 35% sodium hydroxide solution, and the mixed solution was subjected to ultrasonic dispersion treatment, and the temperature was controlled at 65°C. Zirconium propionate was added to the mixed solution, and the mixture was mixed and stirred for 20 minutes. Then, ethyl orthosilicate and sodium lignin sulfonate were added to the mixed solution, and the mixture was allowed to stand for 24 hours to obtain a hydrophobic agent.

[0024] Preferably, the cross-linking agent comprises dipentadienyl vulcanizing agent and dicumyl peroxide, and the mass ratio of the dipentadienyl vulcanizing agent to dicumyl peroxide is 1-3:8-10.

[0025] The foaming agent includes a mixture of dibutyl phthalate, AC foaming agent and zinc oxide, and the mass ratio of the dibutyl phthalate, AC foaming agent and zinc oxide is 1:2:1.

[0026] Preferably, the antioxidant preparation method specifically comprises:

[0027] Add butyl hydroxyanisole and acrylic acid into a reaction bottle, mix them by ultrasonication for 20 minutes, and stir them at a stirring speed of 100-130 r / min to obtain a composite mixture of butyl hydroxyanisole and acrylic acid;

[0028] Take a deacetylated chitosan reagent, then dissolve chitosan in an acetic acid solution to prepare a chitosan solution with a concentration of 0.9-1 mg / mL, adjust the pH value of chitosan to 5-5.5, drop sodium tripolyphosphate into the chitosan solution, and stir at a stirring speed of 300-450 r / min for 20 minutes;

[0029] Add glycerol to the chitosan solution, stir it in a magnetic stirrer at 85°C for 30 minutes, and ultrasonically treat it for 30 minutes. Add nano-titanium dioxide to the chitosan solution, control the temperature at 95°C, and stir and mix it for 30 minutes to obtain a nano suspension.

[0030] Drying the nano suspension by a spray dryer, with a spray pressure of 200-250 kPa, an inlet temperature of 125° C., and an outlet temperature of 68° C. to obtain a dried nano-chitosan and nano-titanium dioxide mixture;

[0031] The butylated hydroxyanisole, acrylic acid compound mixture, nano-chitosan and nano-titanium dioxide mixture were stirred and mixed at a temperature of 65° C., and then ultrasonically treated for 30 minutes to prepare an antioxidant.

[0032] Preferably, the method for preparing modified lignin specifically comprises:

[0033] Sugarcane bagasse and corn stalks are used as raw materials for extracting modified lignin. The sugarcane bagasse and corn stalks are ball-milled in a planetary ball mill for 5-10 minutes to obtain extraction residues. The extraction residues are treated with an alkaline method. During the alkaline treatment, sodium hydroxide and potassium hydroxide alkaline reagents are used for treatment.

[0034] The alkali-treated extract residue infusion was placed in an ultrasonic cleaner for ultrasonic treatment for 30 minutes, the extract residue infusion was allowed to stand for 10 minutes after ultrasonic treatment, and methanol, ethylene glycol, and tetrahydrofuran were used in a volume ratio of 2:1:1 to extract the lignin organic phase;

[0035] Take the lignin organic phase, use a rotary evaporator to remove the organic phase in the lignin organic phase, then place the lignin in a vacuum drying oven, and evacuate the vacuum drying oven. When the vacuum degree in the vacuum drying oven reaches -0.05, stop evacuating. Heat the lignin to 180°C in the vacuum drying oven, keep it warm for 3 hours, cool it, and let it stand for 30 minutes to obtain modified lignin.

[0036] The present invention also provides a method for preparing an EVA prefabricated coiled material for a plastic court runway, the method for preparing an EVA prefabricated coiled material for a plastic court runway specifically comprising:

[0037] Take ethylene-vinyl acetate copolymer and polytetrafluoroethylene, put them into a mixer, heat and stir the ethylene-vinyl acetate copolymer and polytetrafluoroethylene through the mixer, the heating temperature is 120-140° C., the heating time is 30 minutes, after the ethylene-vinyl acetate copolymer and polytetrafluoroethylene are mixed, keep the same temperature to add antioxidant and cross-linking agent, continue heating and stirring for 40 minutes, and obtain a coil melt;

[0038] The coil melt is pumped into a twin-screw extruder, and at the same time, a foaming agent, modified lignin, and a hydrophobic agent are added into the twin-screw extruder. The temperature of the twin-screw extruder is set to 160-180°C;

[0039] The coil melt processed by the twin-screw extruder is extruded, and is calendered into a coil of required thickness by a horizontal three-roll calender. The coil is vulcanized in a coil vulcanizer, and the vulcanized coil is cooled and solidified to obtain an EVA prefabricated coil.

[0040] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0041] In an embodiment of the present invention, an EVA prefabricated coil for a plastic court track is provided, which is based on ethylene-vinyl acetate copolymer and polytetrafluoroethylene, and is added with a hydrophobic agent, an antioxidant and modified lignin, so that the prepared EVA prefabricated coil has high tensile strength and uniform particle size. At the same time, the hydrophobic agent, the antioxidant and the modified lignin work together to ensure the radiation resistance, hydrophobicity and anti-aging properties of the EVA prefabricated coil, and the modified lignin in the raw material has a strong ability to absorb ultraviolet rays, so that the coil has excellent sun protection and UV protection properties.

[0042] In an embodiment of the present invention, a foaming agent is provided, and the foaming agent is composed of dibutyl phthalate, AC foaming agent, and zinc oxide. Zinc oxide as an auxiliary foaming agent can optimize the AC foaming agent, so that the internal pore density of the prepared EVA prefabricated coil is uniform. At the same time, the synergistic cooperation of dibutyl phthalate and the AC foaming agent can improve the softness and ductility of the EVA prefabricated coil, reduce the viscosity of the EVA prefabricated coil, and make the AC foaming agent more easily and evenly dispersed in the EVA prefabricated coil. On the other hand, it can reduce the melting point of the EVA prefabricated coil, so that it can be processed at a lower temperature, and can also prevent the uneven foaming caused by temperature fluctuations.

[0043] In this embodiment, sodium lignin sulfonate is quaternized so that the quaternized sodium lignin sulfonate can be compounded with the nanoparticles in the hydrophobic agent. The obtained hydrophobic agent not only has good dispersibility and excellent ultraviolet absorption performance, but also can significantly improve the antibacterial and mechanical properties of the coil.

[0044] In an embodiment of the present invention, a hydrophobic agent is provided, which is composed of quaternized sodium lignin sulfonate, SiO2 / ZnO composite nanoparticles, and zirconium propionate. Zirconium propionate can exhibit excellent hydrophobic properties in many applications. At the same time, by modifying the surface of SiO2 / ZnO composite nanoparticles with zirconium propionate, a special water-resistant structure can be formed, and the contact angle of the SiO2 / ZnO composite nanoparticles can be changed, so that the surface has extremely strong hydrophobic, water-repellent and waterproof effects. The quaternized sodium lignin sulfonate and SiO2 / ZnO composite nanoparticles also have antibacterial properties, high elongation and self-cleaning properties, thereby significantly improving the physical properties and resistance to chemical corrosion of the EVA prefabricated coil.

[0045] In the embodiment of the present invention, nano-titanium dioxide is added to nano-chitosan to form a nano-chitosan and nano-titanium dioxide mixture, so that nano-chitosan is modified by nano-titanium dioxide, thereby ensuring the antioxidant and antibacterial properties of nano-chitosan, while also being able to solve the disadvantage of poor thermal stability of chitosan, thereby improving the stability and aging resistance of the EVA prefabricated coil. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1It is a schematic diagram of the implementation process of the method for preparing the EVA prefabricated coiled material for the plastic court track provided by the present invention.

[0047] Figure 2 It is a schematic diagram of the implementation process of the method for preparing the hydrophobic agent provided by the present invention.

[0048] Figure 3 It is a schematic diagram of the implementation process of the method for preparing the antioxidant provided by the present invention.

[0049] Figure 4 It is a schematic diagram of the implementation process of the modified lignin preparation method provided by the present invention.

[0050] Figure 5 It is a graph showing the tensile strength at break test result of the present invention.

[0051] Figure 6 It is a graph of the wear resistance test results of the present invention.

[0052] Figure 7 It is a test result diagram of the ultraviolet absorption performance of the present invention. DETAILED DESCRIPTION

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.

[0054] When the existing coiled materials are prepared, the ultraviolet absorber UV-531 is added, which has poor high temperature resistance. When it is mixed with other chemical additives at high temperature, the compatibility may be reduced or migration may occur, which will affect its lasting effect in the coiled materials, thereby accelerating the aging of the coiled materials, resulting in a decrease in the mechanical properties of the coiled materials and a shortened lifespan. In view of the above problems, we have proposed an EVA prefabricated coiled material for plastic court tracks and a preparation method. In short, the EVA prefabricated coiled material for plastic court tracks includes the following raw materials: ethylene-vinyl acetate copolymer, polytetrafluoroethylene, a hydrophobic agent, a cross-linking agent, a foaming agent, an antioxidant, and modified lignin. In an embodiment of the present invention, an EVA prefabricated coil for a plastic court track is provided, which is based on ethylene-vinyl acetate copolymer and polytetrafluoroethylene, and is added with a hydrophobic agent, an antioxidant and modified lignin, so that the prepared EVA prefabricated coil has high tensile strength and uniform particle size. At the same time, the hydrophobic agent, the antioxidant and the modified lignin work together to ensure the radiation resistance, hydrophobicity and anti-aging properties of the EVA prefabricated coil, and the modified lignin in the raw material has a strong ability to absorb ultraviolet rays, so that the coil has excellent sun protection and UV protection properties.

[0055] Example 1

[0056] An embodiment of the present invention provides an EVA prefabricated coil for a plastic court track, wherein the EVA prefabricated coil for a plastic court track includes the following raw materials in parts by weight: 100 parts of ethylene-vinyl acetate copolymer, 1 part of polytetrafluoroethylene, 10 parts of a hydrophobic agent, 1 part of a cross-linking agent, 5 parts of a foaming agent, 1 part of an antioxidant, and 2 parts of modified lignin.

[0057] It should be noted that both ethylene-vinyl acetate copolymer and polytetrafluoroethylene can be finished granular resin products.

[0058] The hydrophobic agent comprises the following raw materials in weight percentage:

[0059] Quaternized sodium lignin sulfonate: 40%;

[0060] SiO2 / ZnO composite nanoparticles: 50%;

[0061] Zirconium propionate: 10%;

[0062] In this embodiment, the cross-linking agent includes dipentadienyl vulcanizing agent and dicumyl peroxide, and the mass ratio of dipentadienyl vulcanizing agent to dicumyl peroxide is 1-3:8-10;

[0063] The foaming agent includes a mixture of dibutyl phthalate, AC foaming agent and zinc oxide, and the mass ratio of the dibutyl phthalate, AC foaming agent and zinc oxide is 1:2:1.

[0064] In an embodiment of the present invention, a foaming agent is provided, and the foaming agent is composed of dibutyl phthalate, AC foaming agent, and zinc oxide. Zinc oxide as an auxiliary foaming agent can optimize the AC foaming agent, so that the internal pore density of the prepared EVA prefabricated coil is uniform. At the same time, the synergistic cooperation of dibutyl phthalate and the AC foaming agent can improve the softness and ductility of the EVA prefabricated coil, reduce the viscosity of the EVA prefabricated coil, and make the AC foaming agent more easily and evenly dispersed in the EVA prefabricated coil. On the other hand, it can reduce the melting point of the EVA prefabricated coil, so that it can be processed at a lower temperature, and can also prevent the uneven foaming caused by temperature fluctuations.

[0065] Example 2

[0066] An embodiment of the present invention provides an EVA prefabricated coil for a plastic court track, wherein the EVA prefabricated coil for a plastic court track includes the following raw materials in parts by weight: 150 parts of ethylene-vinyl acetate copolymer, 10 parts of polytetrafluoroethylene, 30 parts of a hydrophobic agent, 20 parts of a cross-linking agent, 12 parts of a foaming agent, 5 parts of an antioxidant, and 5 parts of modified lignin.

[0067] The hydrophobic agent comprises the following raw materials in weight percentage:

[0068] Quaternized sodium lignin sulfonate: 40%;

[0069] SiO2 / ZnO composite nanoparticles: 50%;

[0070] Zirconium propionate: 10%;

[0071] In this embodiment, the cross-linking agent includes dipentadienyl vulcanizing agent and dicumyl peroxide, and the mass ratio of dipentadienyl vulcanizing agent to dicumyl peroxide is 1-3:8-10;

[0072] The foaming agent includes a mixture of dibutyl phthalate, AC foaming agent and zinc oxide, and the mass ratio of the dibutyl phthalate, AC foaming agent and zinc oxide is 1:2:1.

[0073] Example 3

[0074] An embodiment of the present invention provides an EVA prefabricated coil for a plastic court track, wherein the EVA prefabricated coil for a plastic court track includes the following raw materials in parts by weight: 110 parts of ethylene-vinyl acetate copolymer, 3 parts of polytetrafluoroethylene, 12 parts of a hydrophobic agent, 4 parts of a cross-linking agent, 6 parts of a foaming agent, 2 parts of an antioxidant, and 3 parts of modified lignin.

[0075] The hydrophobic agent comprises the following raw materials in weight percentage:

[0076] Quaternized sodium lignin sulfonate: 40%;

[0077] SiO2 / ZnO composite nanoparticles: 50%;

[0078] Zirconium propionate: 10%;

[0079] In this embodiment, the cross-linking agent includes dipentadienyl vulcanizing agent and dicumyl peroxide, and the mass ratio of dipentadienyl vulcanizing agent to dicumyl peroxide is 1-3:8-10;

[0080] The foaming agent includes a mixture of dibutyl phthalate, AC foaming agent and zinc oxide, and the mass ratio of the dibutyl phthalate, AC foaming agent and zinc oxide is 1:2:1.

[0081] Example 4

[0082] An embodiment of the present invention provides an EVA prefabricated coil for a plastic court track, wherein the EVA prefabricated coil for a plastic court track includes the following raw materials in parts by weight: 140 parts of ethylene-vinyl acetate copolymer, 8 parts of polytetrafluoroethylene, 25 parts of a hydrophobic agent, 15 parts of a cross-linking agent, 11 parts of a foaming agent, 4 parts of an antioxidant, and 4 parts of modified lignin.

[0083] The hydrophobic agent comprises the following raw materials in weight percentage:

[0084] Quaternized sodium lignin sulfonate: 40%;

[0085] SiO2 / ZnO composite nanoparticles: 50%;

[0086] Zirconium propionate: 10%;

[0087] In this embodiment, the cross-linking agent includes dipentadienyl vulcanizing agent and dicumyl peroxide, and the mass ratio of dipentadienyl vulcanizing agent to dicumyl peroxide is 1-3:8-10;

[0088] The foaming agent includes a mixture of dibutyl phthalate, AC foaming agent and zinc oxide, and the mass ratio of the dibutyl phthalate, AC foaming agent and zinc oxide is 1:2:1.

[0089] Example 5

[0090] An embodiment of the present invention provides an EVA prefabricated coil for a plastic court track, wherein the EVA prefabricated coil for a plastic court track includes the following raw materials in parts by weight: 120 parts of ethylene-vinyl acetate copolymer, 5 parts of polytetrafluoroethylene, 20 parts of a hydrophobic agent, 10 parts of a cross-linking agent, 8 parts of a foaming agent, 3 parts of an antioxidant, and 4 parts of modified lignin.

[0091] The hydrophobic agent comprises the following raw materials in weight percentage:

[0092] Quaternized sodium lignin sulfonate: 40%;

[0093] SiO2 / ZnO composite nanoparticles: 50%;

[0094] Zirconium propionate: 10%;

[0095] In this embodiment, the cross-linking agent includes dipentadienyl vulcanizing agent and dicumyl peroxide, and the mass ratio of dipentadienyl vulcanizing agent to dicumyl peroxide is 1-3:8-10;

[0096] The foaming agent includes a mixture of dibutyl phthalate, AC foaming agent and zinc oxide, and the mass ratio of the dibutyl phthalate, AC foaming agent and zinc oxide is 1:2:1.

[0097] like Figure 2 As shown, the method for preparing the hydrophobic agent specifically comprises:

[0098] Step S101, taking sodium lignin sulfonate, dissolving the sodium lignin sulfonate in 6 volumes of deionized water, placing the sodium lignin sulfonate aqueous solution on a 60° C. magnetic stirrer and stirring for 20 minutes, adding 0.5 volumes of ethanol to the sodium lignin sulfonate aqueous solution, stirring for 30 minutes at room temperature, and collecting the precipitate by suction filtration to purify the sodium lignin sulfonate;

[0099] It should be noted that sodium lignin sulfonate is provided by Jinan Hongtai Chemical Co., Ltd. Since sodium lignin sulfonate has a certain hydrophobicity, but also has a strong hydrophilicity, in this embodiment, the sodium lignin sulfonate is quaternized so that the quaternized sodium lignin sulfonate can be composited with the nanoparticles in the hydrophobic agent. The resulting hydrophobic agent not only has good dispersibility and excellent ultraviolet absorption performance, but also can significantly improve the antibacterial and mechanical properties of the coil.

[0100] Step S102, compounding the purified sodium lignin sulfonate with a 30% sodium hydroxide aqueous solution to obtain a 30wt% sodium lignin sulfonate alkaline solution, placing the sodium lignin sulfonate alkaline solution in an oil bath and heating it to 80°C, mixing epichlorohydrin and trimethylolpropane in a volume ratio of 3:1 in a 30% sodium hydroxide aqueous solution to obtain quaternized polyepichlorohydrin, adding the quaternized polyepichlorohydrin to the sodium lignin sulfonate alkaline solution, stirring the sodium lignin sulfonate alkaline solution at a stirring speed of 10-20r / min, keeping the temperature for reaction for 4h, cooling to room temperature, dialyzing the reaction solution, and rotary evaporating to obtain quaternized sodium lignin sulfonate;

[0101] Step S103, zirconium dioxide and propionic acid are mixed in a reactor, the stirring speed is controlled to be 100-120 r / min, ethanol is added to assist the reaction, the reactor is heated to 45° C., after the reaction is completed, the reactor is cooled to room temperature, and zirconium propionate is separated by suction filtration;

[0102] It should be noted that the manufacturer of the zirconium dioxide and propionic acid is Langfang Qianyao Technology Co., Ltd. The reactor is equipped with an electric stirrer, and the model of the electric stirrer is DF-10113 (Guangya Instrument Factory, Zhanjie, Gongyi City). Zirconium propionate is an inorganic compound that is soluble in organic solvents such as ethanol and ether. This physical property enables zirconium propionate to exhibit excellent hydrophobic properties in many applications. At the same time, by modifying the surface of SiO2 / ZnO composite nanoparticles with zirconium propionate, a special water-resistant structure can be formed, which changes the contact angle of SiO2 / ZnO composite nanoparticles and makes the surface extremely hydrophobic, water-repellent and waterproof.

[0103] Step S104, putting silica, anhydrous ethanol and deionized water in a three-necked flask, stirring the mixed solution at a stirring speed of 100-120 r / min for 1.5 h. After the stirring is completed, a silica solution is obtained, and the pH value of the silica aqueous solution is adjusted to 8.5 with ammonia water at 55° C., and γ-aminopropyltriethoxysilane is added dropwise into the three-necked flask. After reacting for 2.5 h, the temperature of the three-necked flask is raised to 80° C., and the silica is modified to obtain an amino-modified silica solution;

[0104] Step S105, taking zinc oxide, dispersing the zinc oxide in 8 times the volume of deionized water, stirring evenly for 30 minutes, then dropping the zinc oxide suspension into the amino-modified silica solution, stirring evenly for 2 hours by ultrasonication, and washing with deionized water and anhydrous ethanol in a volume ratio of 1:1 to obtain SiO2 / ZnO composite nanoparticles;

[0105] Step S106, dissolving SiO2 / ZnO composite nanoparticles in 35% sodium hydroxide solution, subjecting the mixed solution to ultrasonic dispersion treatment, and controlling the temperature to 65°C, adding zirconium propionate into the mixed solution, mixing and stirring for 20 minutes, and then adding ethyl orthosilicate and sodium lignin sulfonate to the mixed solution, and leaving it to stand for 24 hours to obtain a hydrophobic agent.

[0106] In an embodiment of the present invention, a hydrophobic agent is provided, which is composed of quaternized sodium lignin sulfonate, SiO2 / ZnO composite nanoparticles, and zirconium propionate. Zirconium propionate can exhibit excellent hydrophobic properties in many applications. At the same time, by modifying the surface of SiO2 / ZnO composite nanoparticles with zirconium propionate, a special water-resistant structure can be formed, and the contact angle of the SiO2 / ZnO composite nanoparticles can be changed, so that the surface has extremely strong hydrophobic, water-repellent and waterproof effects. The quaternized sodium lignin sulfonate and SiO2 / ZnO composite nanoparticles also have antibacterial properties, high elongation and self-cleaning properties, thereby significantly improving the physical properties and resistance to chemical corrosion of the EVA prefabricated coil.

[0107] The antioxidant comprises the following raw materials in weight percentage:

[0108] Nano chitosan: 50%;

[0109] Nano titanium dioxide: 20%;

[0110] Acrylic acid: 15%;

[0111] Butylated hydroxyanisole: 15%.

[0112] It should be noted that the deacetylation degree of chitosan is 85% (Jinan Haidebei Marine Bioengineering Co., Ltd.), the purity of nano-titanium dioxide is 99% (Hebei Weicai Pigment Co., Ltd.), acrylic acid is analytically pure AR (Shandong Luying Chemical Co., Ltd.), and butylated hydroxyanisole (Hebei Runbu Biotechnology Co., Ltd.).

[0113] like Figure 3 As shown, the antioxidant preparation method specifically includes:

[0114] Step S201, adding butyl hydroxyanisole and acrylic acid into a reaction bottle, ultrasonically mixing for 20 minutes, and stirring at a stirring speed of 100-130 r / min to obtain a composite mixture of butyl hydroxyanisole and acrylic acid;

[0115] In this embodiment, a numerically controlled ultrasonic cleaner KQ-100DE is used for ultrasonic mixing, and a heated magnetic stirrer SH-3 is used for stirring and mixing.

[0116] Step S202, taking a deacetylated chitosan reagent, then dissolving chitosan in an acetic acid solution to prepare a chitosan solution with a concentration of 0.9-1 mg / mL, adjusting the pH value of the chitosan to 5-5.5, dropping sodium tripolyphosphate into the chitosan solution, and stirring at a stirring speed of 300-450 r / min for 20 min;

[0117] Step S203, adding glycerol to the chitosan solution, placing it in a magnetic stirrer at 85°C and stirring for 30 minutes, ultrasonically treating it for 30 minutes, adding nano titanium dioxide to the chitosan solution, controlling the temperature at 95°C, stirring and mixing for 30 minutes, and obtaining a nano suspension;

[0118] Step S204, drying the nano suspension by a spray dryer, with the spray pressure being 200-250 kPa, the inlet temperature being 125° C., and the outlet temperature being 68° C., to obtain a dried nano-chitosan and nano-titanium dioxide mixture;

[0119] In the embodiment of the present invention, nano-titanium dioxide is added to nano-chitosan to form a nano-chitosan and nano-titanium dioxide mixture, so that nano-chitosan is modified by nano-titanium dioxide, thereby ensuring the antioxidant and antibacterial properties of nano-chitosan, while also being able to solve the disadvantage of poor thermal stability of chitosan, thereby improving the stability and aging resistance of the EVA prefabricated coil.

[0120] Step S205, stirring and mixing butylated hydroxyanisole, acrylic acid compound mixture, nano-chitosan, and nano-titanium dioxide mixture at 65° C., and then ultrasonically treating for 30 minutes to obtain an antioxidant.

[0121] The present invention also provides a method for preparing modified lignin. Figure 4 The schematic diagram of the process flow of the modified lignin preparation method is shown, and the modified lignin preparation method specifically includes:

[0122] Step S301, using bagasse and corn stalks as raw materials for modified lignin extraction, using a planetary ball mill to ball-mill the bagasse and corn stalks for 5-10 minutes to obtain extraction residues, and treating the extraction residues with an alkaline method, wherein sodium hydroxide and potassium hydroxide alkaline reagents are used for the alkaline treatment;

[0123] Step S302, placing the alkali-treated extraction residue infusion in an ultrasonic cleaner for ultrasonic treatment for 30 minutes, leaving the extraction residue infusion to stand for 10 minutes after ultrasonic treatment, and extracting the lignin organic phase using methanol, ethylene glycol, and tetrahydrofuran in a volume ratio of 2:1:1.

[0124] Step S303, taking the lignin organic phase, using a rotary evaporator to remove the organic phase in the lignin organic phase, then placing the lignin in a vacuum drying oven, and evacuating the vacuum drying oven. When the vacuum degree in the vacuum drying oven reaches -0.05, stop evacuating. The vacuum drying oven heats the lignin to 180°C, keeps it warm for 3 hours, cools it, and stands for 30 minutes to obtain modified lignin.

[0125] It should be noted that in the embodiments of the present invention, by vacuum drying the extracted lignin, the acetyl group of the hemicellulose mixed in the lignin will produce acetic acid through a hydrolysis reaction, and the acetic acid will react with the lignin, and the lignin will undergo an esterification reaction, thereby introducing more carbonyl groups into the lignin.

[0126] In the embodiments of the present invention, the modified lignin raw materials are low-cost and easily available bagasse and corn stalks, thereby reducing the processing cost of the EVA prefabricated coil. At the same time, the recovery efficiency of lignin is improved by the coordinated cooperation of ball milling, alkaline treatment and ultrasonic treatment, and the carbonyl group is introduced and its aromatic structure and active group are utilized to enhance the absorption capacity of ultraviolet rays, so that the coil has excellent ultraviolet protection performance.

[0127] In an embodiment of the present invention, a method for preparing an EVA prefabricated coil for a plastic court track is provided. Figure 1 The schematic diagram of the process flow of the method for preparing the EVA prefabricated coiled material for the plastic court track is shown. The method for preparing the EVA prefabricated coiled material for the plastic court track specifically includes:

[0128] Step S10, taking ethylene-vinyl acetate copolymer and polytetrafluoroethylene, putting the ethylene-vinyl acetate copolymer and polytetrafluoroethylene into a mixer, heating and stirring the ethylene-vinyl acetate copolymer and polytetrafluoroethylene by the mixer, the heating temperature is 120-140° C., the heating time is 30 minutes, after the ethylene-vinyl acetate copolymer and polytetrafluoroethylene are mixed, adding an antioxidant and a cross-linking agent at the same temperature, and continuing heating and stirring for 40 minutes to obtain a coil melt;

[0129] Step S20, pumping the coil melt into a twin-screw extruder, and simultaneously adding a foaming agent, modified lignin, and a hydrophobic agent into the twin-screw extruder, and setting the temperature of the twin-screw extruder to 160-180°C.

[0130] Step S30, the coil melt processed by the twin-screw extruder is extruded, and is rolled into a coil of required thickness by a horizontal three-roll calender, and the coil is vulcanized by a coil vulcanizer, and the vulcanized coil is cooled and solidified to obtain an EVA prefabricated coil.

[0131] Comparative Example 1

[0132] The raw materials and preparation method of this comparative example are similar to those of Example 5, except that the EVA prefabricated coil raw materials do not include: hydrophobic agent and antioxidant. The raw materials include the following raw materials in parts by weight: 140 parts of ethylene-vinyl acetate copolymer, 8 parts of polytetrafluoroethylene, 15 parts of cross-linking agent, 11 parts of foaming agent, and 3 parts of modified lignin.

[0133] Comparative Example 2

[0134] The raw materials and preparation method of this comparative example are similar to those of Example 5, except that the EVA prefabricated coil raw materials do not include modified lignin. The raw materials include the following raw materials in parts by weight: 110 parts of ethylene-vinyl acetate copolymer, 3 parts of polytetrafluoroethylene, 12 parts of hydrophobic agent, 4 parts of cross-linking agent, 6 parts of foaming agent, and 2 parts of antioxidant.

[0135] Comparative Example 3

[0136] The raw materials and preparation method of this comparative example are similar to those of Example 5, except that the EVA prefabricated coil raw materials do not include a hydrophobic agent. The raw materials include the following raw materials in parts by weight: 120 parts of ethylene-vinyl acetate copolymer, 4 parts of polytetrafluoroethylene, 12 parts of a cross-linking agent, 8 parts of a foaming agent, 3 parts of an antioxidant, and 4 parts of modified lignin.

[0137] Comparative Example 4

[0138] The raw materials and preparation method of this comparative example are similar to those of Example 5, except that the EVA prefabricated coil raw materials do not include an antioxidant. The raw materials include the following raw materials in parts by weight: 130 parts of ethylene-vinyl acetate copolymer, 5 parts of polytetrafluoroethylene, 20 parts of a hydrophobic agent, 12 parts of a cross-linking agent, 7 parts of a foaming agent, and 4 parts of modified lignin.

[0139] Comparative Example 5

[0140] The raw materials and preparation method of this comparative example are similar to those of Example 5, except that the EVA prefabricated coil raw materials do not include: hydrophobic agent, antioxidant, and modified lignin. The raw materials include the following raw materials in parts by weight: 140 parts of ethylene-vinyl acetate copolymer, 8 parts of polytetrafluoroethylene, 15 parts of cross-linking agent, and 11 parts of foaming agent.

[0141] Performance Test:

[0142] Test Example 1

[0143] The EVA prefabricated coils prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were taken to test the tensile strength at break of the EVA prefabricated coils. Before the test, the EVA prefabricated coils prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were left to stand at room temperature for 48 hours. During the test, the clamping distance was 200 mm, the tensile speed was 50 mm / min, and the test results of tensile strength at break and elongation at break are shown in Table 1. Figure 5 A graph showing the tensile strength at break test results is shown.

[0144] Table 1

[0145]

[0146] It can be seen from Table 1 that Examples 1-5 of the present invention have better tensile properties and toughness than Comparative Examples 1-5. It can be concluded that the synergistic combination of the hydrophobic agent, the antioxidant, and the modified lignin has a positive effect on increasing the mechanical properties of the coil.

[0147] Test Example 2

[0148] The EVA preformed coils prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were taken, and the wear resistance of the EVA preformed coils was tested using an EVA outsole wear tester. Before the test, the EVA preformed coils prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were left to stand at room temperature for 48 hours, and then the EVA preformed coil samples were glued to a rubber wheel, and the rubber wheel was in contact with a grinding wheel at an angle of 15° for rolling friction, and the wear volume of the EVA preformed coil was measured. The wear resistance test results are shown in Tables 2 and Figure 6 shown.

[0149] Table 2

[0150]

[0151] It can be seen from Table 2 that embodiments 1-5 of the present invention have better wear resistance than comparative embodiments 1-5. It can be concluded that embodiments 1-5 of the present invention have better wear resistance and are suitable for laying plastic court tracks.

[0152] Test Example 3

[0153] The EVA preformed coils prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were taken to test the ultraviolet absorption performance of the EVA preformed coils. Before the test, the EVA preformed coils prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were left to stand at room temperature for 48 hours. The EVA preformed coil samples were pasted on the surface of the substrate, and then the ultraviolet transmittance in the UVA region (320nm-400nm) and the UVB region (290nm-320nm) was tested using an ultraviolet spectrophotometer, and the sun protection factor was calculated based on the ultraviolet transmittance. The ultraviolet absorption performance test results are shown in Tables 3 and Figure 7 shown.

[0154] Table 3

[0155]

[0156] As can be seen from Table 3, Examples 1-5 of the present invention have better sun protection and UV absorption performance than Comparative Examples 1-5. In Examples 1-5 of the present invention, the modified lignin introduces a carbonyl group and utilizes its aromatic structure and active groups to enhance the ability to absorb UV rays, thereby making the coil have excellent UV protection performance.

[0157] In summary, the present invention provides an EVA prefabricated coil for a plastic court runway and a preparation method. In an embodiment of the present invention, an EVA prefabricated coil for a plastic court runway is provided. Ethylene-vinyl acetate copolymer and polytetrafluoroethylene are used as base materials, and a hydrophobic agent, an antioxidant and modified lignin are added, so that the prepared EVA prefabricated coil has high tensile strength and uniform particle size. At the same time, the hydrophobic agent, the antioxidant and the modified lignin cooperate to ensure the radiation resistance, hydrophobicity and anti-aging properties of the EVA prefabricated coil, and the modified lignin in the raw material has a strong ability to absorb ultraviolet rays, so that the coil has excellent sun protection and UV protection properties.

[0158] It should be noted that, for the above-mentioned embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the described order of actions, because according to the present invention, some steps may be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and modules involved are not necessarily required by the present invention.

[0159] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the scope of protection of the invention. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on these embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in this field can still combine, add, delete or make other adjustments to the features in the various embodiments of the present invention according to the circumstances without conflict, without making creative work, so as to obtain different other technical solutions that do not deviate from the concept of the present invention in essence, and these technical solutions also belong to the scope of protection of the present invention.

Claims

1. The EVA prefabricated coil for plastic court track is characterized by: The EVA prefabricated coil for the plastic court track includes the following raw materials in parts by weight: 100-150 parts of ethylene-vinyl acetate copolymer, 1-10 parts of polytetrafluoroethylene, 10-30 parts of hydrophobic agent, 1-20 parts of cross-linking agent, 5-12 parts of foaming agent, 1-5 parts of antioxidant, and 2-5 parts of modified lignin; The hydrophobic agent comprises the following raw materials in weight percentage: Quaternized sodium lignin sulfonate: 40%; SiO2 / ZnO composite nanoparticles: 50%; Zirconium propionate: 10%; The antioxidant comprises the following raw materials in weight percentage: Nano chitosan: 50%; Nano titanium dioxide: 20%; Acrylic acid: 15%; Butylated hydroxyanisole: 15%; The antioxidant preparation method specifically comprises: Add butyl hydroxyanisole and acrylic acid into a reaction bottle, mix them by ultrasonication for 20 minutes, and stir them at a stirring speed of 100-130 r / min to obtain a composite mixture of butyl hydroxyanisole and acrylic acid; Take a deacetylated chitosan reagent, then dissolve chitosan in an acetic acid solution to prepare a chitosan solution with a concentration of 0.9-1 mg / mL, adjust the pH value of chitosan to 5-5.5, drop sodium tripolyphosphate into the chitosan solution, and stir at a stirring speed of 300-450 r / min for 20 minutes; Add glycerol to the chitosan solution, stir it in a magnetic stirrer at 85°C for 30 minutes, and ultrasonically treat it for 30 minutes. Add nano-titanium dioxide to the chitosan solution, control the temperature at 95°C, and stir and mix it for 30 minutes to obtain a nano suspension. Drying the nano suspension by a spray dryer, with a spray pressure of 200-250 kPa, an inlet temperature of 125° C., and an outlet temperature of 68° C. to obtain a dried nano-chitosan and nano-titanium dioxide mixture; The butylated hydroxyanisole, acrylic acid compound mixture, nano-chitosan and nano-titanium dioxide mixture were stirred and mixed at 65°C, and then ultrasonically treated for 30 minutes to prepare an antioxidant. The modified lignin preparation method specifically comprises: Sugarcane bagasse and corn stalks are used as raw materials for extracting modified lignin. The sugarcane bagasse and corn stalks are ball-milled in a planetary ball mill for 5-10 minutes to obtain extraction residues. The extraction residues are treated with an alkaline method. During the alkaline treatment, sodium hydroxide and potassium hydroxide alkaline reagents are used for treatment. The alkali-treated extract residue infusion was placed in an ultrasonic cleaner for ultrasonic treatment for 30 minutes, the extract residue infusion was allowed to stand for 10 minutes after ultrasonic treatment, and methanol, ethylene glycol, and tetrahydrofuran were used in a volume ratio of 2:1:1 to extract the lignin organic phase; Take the lignin organic phase, use a rotary evaporator to remove the organic phase in the lignin organic phase, then place the lignin in a vacuum drying oven, and evacuate the vacuum drying oven. When the vacuum degree in the vacuum drying oven reaches -0.05, stop evacuating. Heat the lignin to 180°C in the vacuum drying oven, keep it warm for 3 hours, cool it, and let it stand for 30 minutes to obtain modified lignin.

2. The EVA prefabricated coil for a plastic court track as claimed in claim 1, characterized in that: The EVA prefabricated coil for the plastic court track includes the following raw materials in parts by weight: 110-140 parts of ethylene-vinyl acetate copolymer, 3-8 parts of polytetrafluoroethylene, 12-25 parts of hydrophobic agent, 4-15 parts of cross-linking agent, 6-11 parts of foaming agent, 2-4 parts of antioxidant, and 3-4 parts of modified lignin.

3. The EVA prefabricated coil for a plastic court track as claimed in claim 1, characterized in that: The method for preparing the hydrophobic agent specifically comprises: Take sodium lignin sulfonate, dissolve the sodium lignin sulfonate in 6 times the volume of deionized water, place the sodium lignin sulfonate aqueous solution on a 60°C magnetic stirrer and stir for 20 minutes, add 0.5 times the volume of ethanol to the sodium lignin sulfonate aqueous solution, stir for 30 minutes at room temperature, and collect the precipitate by suction filtration to purify the sodium lignin sulfonate; The purified sodium lignin sulfonate is compounded with a 30% sodium hydroxide aqueous solution to obtain a 30wt% sodium lignin sulfonate alkaline solution, the sodium lignin sulfonate alkaline solution is placed in an oil bath and heated to 80°C, epichlorohydrin and trimethylolpropane are mixed in a 30% sodium hydroxide aqueous solution at a volume ratio of 3:1 to obtain quaternized polyepichlorohydrin, the quaternized polyepichlorohydrin is added to the sodium lignin sulfonate alkaline solution, the sodium lignin sulfonate alkaline solution is stirred at a stirring speed of 10-20r / min, the reaction is kept warm for 4h, and then cooled to room temperature, the reaction solution is dialyzed, and rotary evaporated to obtain quaternized sodium lignin sulfonate; Zirconium dioxide and propionic acid are mixed in a reactor, the stirring speed is controlled to be 100-120 r / min, ethanol is added to assist the reaction, the reactor is heated to 45° C., after the reaction is completed, the reactor is cooled to room temperature, and zirconium propionate is separated by suction filtration; Put silica, anhydrous ethanol and deionized water in a three-necked flask, stir the mixed solution at a speed of 100-120 r / min for 1.5 h. After stirring, a silica solution is obtained. Ammonia water is used to adjust the pH value of the silica aqueous solution to 8.5 at 55 ° C. γ-aminopropyltriethoxysilane is taken and added dropwise into the three-necked flask. After reacting for 2.5 h, the three-necked flask is heated to 80 ° C. The silica is modified to obtain an amino-modified silica solution.

4. The EVA prefabricated coil for a plastic court track as claimed in claim 3, characterized in that: The method for preparing the hydrophobic agent specifically further comprises: Take zinc oxide, disperse it in 8 times the volume of deionized water, stir it evenly for 30 minutes, then add the zinc oxide suspension dropwise into the amino-modified silica solution, stir it evenly for 2 hours by ultrasonic, and wash it with deionized water and anhydrous ethanol in a volume ratio of 1:1 to obtain SiO2 / ZnO composite nanoparticles; SiO2 / ZnO composite nanoparticles were dissolved in 35% sodium hydroxide solution, and the mixed solution was subjected to ultrasonic dispersion treatment, and the temperature was controlled at 65°C. Zirconium propionate was added to the mixed solution, and the mixture was mixed and stirred for 20 minutes. Then, ethyl orthosilicate and sodium lignin sulfonate were added to the mixed solution, and the mixture was allowed to stand for 24 hours to obtain a hydrophobic agent.

5. The EVA prefabricated coil for a plastic court track as claimed in claim 1, characterized in that: The cross-linking agent includes a dipentadienyl vulcanizing agent and dicumyl peroxide, and the mass ratio of the dipentadienyl vulcanizing agent to dicumyl peroxide is 1-3:8-10; The foaming agent includes a mixture of dibutyl phthalate, AC foaming agent and zinc oxide, and the mass ratio of the dibutyl phthalate, AC foaming agent and zinc oxide is 1:2:

1.

6. A method for preparing an EVA prefabricated coil for a plastic court runway, for preparing the EVA prefabricated coil for a plastic court runway as claimed in any one of claims 1 to 5, characterized in that: The method for preparing the EVA prefabricated coiled material for the plastic court track specifically comprises: Take ethylene-vinyl acetate copolymer and polytetrafluoroethylene, put them into a mixer, heat and stir the ethylene-vinyl acetate copolymer and polytetrafluoroethylene through the mixer, the heating temperature is 120-140° C., the heating time is 30 minutes, after the ethylene-vinyl acetate copolymer and polytetrafluoroethylene are mixed, keep the same temperature to add antioxidant and cross-linking agent, continue heating and stirring for 40 minutes, and obtain a coil melt; The coil melt is pumped into a twin-screw extruder, and a foaming agent, modified lignin, and a hydrophobic agent are simultaneously added into the twin-screw extruder. The temperature of the twin-screw extruder is set at 160-180°C.

7. The method for preparing the EVA prefabricated coil for the plastic court track according to claim 6, characterized in that: The method for preparing the EVA prefabricated coiled material for the plastic court track specifically includes: The coil melt processed by the twin-screw extruder is extruded, and is calendered into a coil of required thickness by a horizontal three-roll calender. The coil is vulcanized in a coil vulcanizer, and the vulcanized coil is cooled and solidified to obtain an EVA prefabricated coil.